This presentation is the property of its rightful owner.
1 / 9

# 3.5 More on Solving Equations Goal: PowerPoint PPT Presentation

3.5 More on Solving Equations Goal: To solve equations by first getting all variables to the same side of the equation. Steps to solve multi-step linear equations. If there are ( ) distribute Collect like terms on same side. Move variables to same side of equation. (APE)

3.5 More on Solving Equations Goal:

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -

#### Presentation Transcript

3.5 More on Solving Equations

Goal:

• To solve equations by first getting all variables to the same side of the equation

Steps to solve multi-step linear equations

• If there are ( ) distribute

• Collect like terms on same side.

• Move variables to same side of equation. (APE)

• Move the constant to the other side of the equation (APE)

• Solve for x using the (MPE)

+ 3x

+ 3x

### If there are variables on both sides of the equation….

• Eliminate the variable from one side using the Addition Property of Equality

2x – 2 = -3x + 3

5x – 2 = + 3

### Solve for x:

+3m

+3m

-5

-5

• Collect like terms on the same side first

• Eliminate the variable from one side using the Addition Property of Equality

6m +5 – 2m = 10 – 3m +16

4m +5 = 26 – 3m

7m +5 = 26

7m = 21

m =3

+3m

+3m

-5

-5

6m +5 – 2m = 10 – 3m +16

4m +5 = 26 – 3m

7m +5 = 26

7m = 21

m =3

### 3(n - 2) – 1 = 2 – 5(n + 5)

3n - 6 – 1 = 2 – 5(n + 5)

3n - 6 – 1 = 2 – 5n - 25

3n - 7 = -23 – 5n

5n +

+5n

8n - 7 = -23

+7

+7

8n = -16

n =-2

3(2y +7) = 30 + 7(y - 1)

You try this one and raise your hand once you get the answer!

y = -2